Case report of an elderly woman with atypical imaging for primary central nervous system lymphoma who needed a brain biopsy for diagnosis. Issue 8 (August 2021) - Matsuzono, Kosuke; Yagisawa, Tomoya; Ohtani, Keisuke; Ishishita, Yohei; Yamaguchi, Takashi; Mashiko, Takafumi; Ozawa, Tadashi; Koide, Reiji; Tanaka, Ryota; Kawai, Kensuke; Fujimoto, Shigeru
Primary central nervous system lymphoma (PCNSL) is a rare form of non-Hodgkin lymphoma, but its diagnosis is challenging in some cases. A brain biopsy is the gold standard for diagnosing PCNSL, but its invasiveness can be problematic. Thus, noninvasive imaging examinations have been developed for the pre-surgical diagnosis of PCNSL, including gadolinium-enhanced magnetic resonance imaging (MRI), 123 I-N-isopropyl-p-iodoamphetamine single-photon emission computed tomography ( 123 I-IMP SPECT), and positron emission tomography with 18 F-fluorodeoxyglucose ( 18 F-FDG PET). Here, we report the case of a 71-year-old woman with negative imaging findings for PCNSL, but who was diagnosed with PCNSL by a brain biopsy and histological analysis. Her imaging results were negative for gadolinium-enhanced cranial MRI, with low uptake in 123 I-IMP SPECT and hypometabolism in 18 F-FDG PET. However, a stereotactic brain biopsy from an abnormal lesion revealed that many round cells had infiltrated into the brain. Moreover, many infiltrating cells were positive for cluster of differentiation (CD)20 and CD79a, and proliferation marker protein Ki-67-positive cells accounted for nearly 80% of all cells. Based on these results, our final pathological diagnosis was PCNSL. The present case highlights the possibility of a PCNSL diagnosis even when all imaging-related examinations display negative results.